Resolving cryptic species with morphology and DNA; thrips as a potential biocontrol agent of Brazilian peppertree, with a new species and overview of Pseudophilothrips (Thysanoptera) - Mound, L. A.; Wheeler, G. S.; Williams, D. A. (Zootaxa, 2010)
Molecular and morphological evidence is presented to support the description of a second species of Pseudophilothrips from Brazil in association with Schinus terebinthifolius, an invasive weedy tree in North America. Pseudophilothrips is here recognized as a weakly defined genus comprising 13 described species from the Americas. This genus is presumably derived from within, rather than sister-genus to, the worldwide genus Liothrips of leaf-feeding species.